Pengaruh Transparansi, Akuntabilitas, Dan Kepercayaan Publik Dalam Pengelolaan Dana Desa Terhadap Kemajuan Desa Kemiri Sidoarjo (International Forum of Researchers and Lecturers, 2024)
The purpose of this study was to examine the influence of transparency, accountability, and public trust in the management of village funds on village progress, especially in Kemiri Village, Sidoarjo District. The population studied in this study was Kemiri Village, and the research methodology used was descriptive quantitative sampling with a sample size of 100 respondents. Researchers used SPSS 22 (Statistical Product and Service Solution), which includes determination test (R2), t test, f test, and multiple regression analysis test. The research findings show that although the public trust variable has little effect on village progress, the transparency and accountability variables have a positive and significant effect on the progress of Kemiri village.